The role of motivation in learning English as a foreign language - Dwi Riyanti (UPT Bahasa Universitas Tanjungpura, 2019)
Motivation is undoubtedly an important factor in learning foreign languages. Yet, in English as foreign language context, like Indonesia, especially in West Kalimantan, not all students are motivated to learn English, a compulsory foreign language for secondary students. Thus, it is a necessity that teachers know how to increase students’ motivation. This paper analyses the issue of motivation in learning English as a compulsory subject in a foreign language context which can be useful for teachers and students to know what why motivation is important in learning foreign languages. Through reviewing related literatures to motivation, this paper outlines the role of motivation in learning a foreign language, and the problems of low motivation commonly found in EFL contexts. It also discusses some possible causes of low motivation as well as elaborates ways to increase students’ motivation.